The body owner's diary - Coonan, Wayne; Worsley, A. (Anthony), 1945-; Australia. Education Research and Development Committee ([Adelaide, S. Aust.] : W. Coonan and A. Worsley, 1981)
A book for recording performances in a personal health programme.
Cover title.
Produced for an E.R.D.C. project.
Keywords: Health; Physical fitness